2005
DOI: 10.1590/s1517-86922005000100001
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do esforço percebido na determinação da velocidade crítica em corrida aquática

Abstract: The linear relation between exercise intensity and the increase rate of the neuromuscular activity assessed by electromyography allows the estimation of the fatigue threshold, which would be the intensity that could be maintained indefinitely without presenting increase on the electromyography signals along time. It has been hypothesized that the subjetive perception of exertion would behave similarly to the neuromuscular activity and that a perceived exertion threshold (PET) identified similarly to the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 24 publications
2
9
0
26
Order By: Relevance
“…Moreover, Gibson et al (30) suggested that the processing of the perceived exertion is also altered by cognitive signals, such as the memory of a training session previously conducted and the motivation at the moment of the task. Thereby, we believe that differently from other studies in which there was the control of contextual variables that may interfere in the PE (9,11,22) , the intention to exercise to the limit in real situations of sports practice, leads to a time dissociation of the PE with the HR and with the exercise intensity.…”
Section: Ementioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, Gibson et al (30) suggested that the processing of the perceived exertion is also altered by cognitive signals, such as the memory of a training session previously conducted and the motivation at the moment of the task. Thereby, we believe that differently from other studies in which there was the control of contextual variables that may interfere in the PE (9,11,22) , the intention to exercise to the limit in real situations of sports practice, leads to a time dissociation of the PE with the HR and with the exercise intensity.…”
Section: Ementioning
confidence: 61%
“…Thus, it is probable that the recreational runners have constantly adjusted the υ _ in a manner inverse to the contribution of the glycolytic system, at least up to the one before the last lap. It is known that with the participation of the glycolytic system in protocols with continuous load, an increase of the PE proportional to the anaerobic mobilization rate is observed (11) . However, such discourse should be cautiously interpreted, since in the present investigation no measurement of this physiological variable was taken.…”
Section: Ementioning
confidence: 99%
See 2 more Smart Citations
“…Nakamura et al (2005), observaram em treze indivíduos de ambos os sexos (23,0 ± 2,5 anos), em percentuais superiores à VC, que o EP aumentava em função do tempo a uma taxa proporcional à intensidade na corrida aquática. O menor valor de correlação (tau = 0,544) encontrado no presente estudo entre o EP e a [LA] pode ser explicado pelo papel do EP no controle da tolerância às demandas da intensidade do exercício: parece que nem sempre o EP pode aumentar em função do incremento da [LA] (acidose metabólica) em uma série de treinamento intervalado (ALBERTUS et al, 2005;CREWE;TUCKER;NOAKES, 2008).…”
Section: Familiarização Com a Escala De 15 Pontos De Borgunclassified